Bio-inspired graphene-based nano-systems for biomedical applications. (21st September 2021) - Bhardwaj, Sheetal Kaushik; Mujawar, Mubarak; Mishra, Yogendra Kumar; Hickman, Nicoleta; Chavali, Murthy; Kaushik, Ajeet
Abstract: The increasing demands of environmentally sustainable, affordable, and scalable materials have inspired researchers to explore greener nanosystems of unique properties which can enhance the performance of existing systems. Such nanosystems, extracted from nature, are state-of-art high-performance nanostructures due to intrinsic hierarchical micro/nanoscale architecture and generous interfacial interactions in natural resources. Among several, bio-inspired nanosystems graphene nanosystems have emerged as an essential nano-platform wherein a highly electroactive, scalable, functional, flexible, and adaptable to a living being is a key factor. Preliminary investigation project bio-inspired graphene nanosystems as a multi-functional nano-platform suitable for electronic devices, energy storage, sensors, and medical sciences application. However, a broad understanding of bio-inspired graphene nanosystems and their projection towards applied application is not well-explored yet. Considering this as a motivation, this mini-review highlights the following; the emergence of bio-inspired graphene nanosystems, over time development to make them more efficient, state-of-art technology, and potential applications, mainly biomedical including biosensors, drug delivery, imaging, and biomedical systems. The outcomes of this review will certainly serve as a guideline to motivate scholars to design and develop novel bio-inspired graphene nanosystems to develop greener, affordable, and scalable next-generation biomedical systems.